Four-year reciprocal relationships between personality and functional ability in older adults with and without sensory impairment: focus on neuroticism and agreeableness. (3rd June 2018) - Wettstein, Markus; Wahl, Hans-Werner; Heyl, Vera
ABSTRACT: Objectives: Personality traits have been found to influence health and functional ability (FA) via multiple pathways. However, personality traits may also change in reaction to constraints in FA, particularly in more vulnerable individuals with high risk of decline in independent functioning in daily life (e.g. older adults with sensory impairment). Therefore, conceptually anchored in the World Health Organization's International Classification of Functioning, Disability and Health (ICF model), this study investigated reciprocal relationships between personality, focusing on neuroticism and agreeableness, and indicators of FA (i.e. activities of daily living and subjective autonomy) as well as the potentially moderating role of sensory impairment status. Method: The study sample consisted of 387 older adults (mean age at T1: M = 82.50 years, SD = 4.71 years) who were either sensory impaired (SI; i.e. visually or hearing impaired) or sensory unimpaired (UI). A total of 168 individuals were reassessed four years later. Results: Depending on sensory status, personality acted both as predictor and as outcome of FA. Neuroticism was more strongly related with later FA outcomes in SI than in UI individuals. FA variables, in turn, were significant predictors of later neuroticism in UI older adults only and of later agreeableness in SI individuals only. Conclusion: These findings suggest that the late-life personality-FA interplay needs to be considered bidirectional, and the direction of associations varies systematically as a function of sensory impairment status.